Alteration of endogenous fatty acids profile and lipid metabolism in rats caused by a high-colleseed oil and a high-sunflower oil diet - Li, Ruizhi; Tan, Chin Ping; Xu, Yong Jiang; Liu, Yuanfa (Wiley-VCH Verlag, 2021)
Dietary fat has an important influence on mammalian lipid homeostasis. However, the relationship between dietary fat types and endogenous fatty acids (FAs) in organs as well as lipid homeostasis remains unclear enough. In this study, rats are randomly divided into a control group (CN), a high-colleseed oil group (COG), and a high-sunflower oil group (SOG). FAs profile in liver and visceral fats of rats in two high-fat (HF) diet groups is compared with that in CN. Oleic, γ-linolenic, eicosadienoic, and arachidonic acid accumulate in COG liver or visceral fats, but the levels of linoleic, eicosadienoic, docosanoic, and dihomo-γ-linolenic acid decrease in COG visceral fats. However, these FAs levels increased in SOG liver or visceral fats except dihomo-γ-linolenic and arachidonic acid which changed insignificantly. The trend of initial upregulation and then downregulation of lipid metabolism-related genes expression is noted in COG liver, including stearoyl-CoA desaturase. Upregulation of adiponectin (ADPN) expression in visceral fats and downregulation of ADPN receptor 2 (Adipo-R2) expression in livers of both HF groups are observed. Correlation analysis revealed positive correlations between specific FAs content and ADPN expression level. Negative correlations are observed between Adipo-R2 expression and the content of oleic, linoleic, and γ-linolenic acid in the SOG liver.